Epr of Free Radicals Forming When Exposed to X-Ray Radiation from Acidic Organic Polymer - Ibrahim, Ibrahim A.; Mansour, Saber E.; Desouky, Osama Amine (Al-Mukhtar Journal of Sciences, 2009)
Using a highly effective method of destruction of solid polymers (X-ray) and a highly selective method of identifying paramagnetic centers (EPR), it was possible to reveal the characteristics of the molecular structure of originally diamagnetic substances. A substantial difference of PMAA from PAA and PVT is the presence of lateral methyl groups, which is responsible for the differences in structure of macromolecular lumps of these polymers. When synthesizing PMAA in the hydrocarbon environment, hydrophobic carboxyl groups appear to be localized in inner regions of the lumps thus enabling contact of hydrophobic metlryl groups with liexane. The Cu2+ ions in PMAA lrave the role of a radio protector by substantially decreasing tire radiation yield of free radicals through redox processes. Unlike Cu2+ ions, the Co2, and Ni2؛ ions in PMAA do not undergo redox reactions with free I’adicals, at least at room temperabire.